Catalyzing Change: Analyzing the Dynamics and Impact of EndSARS Protests in Nigeria - Emoedumhe, Inagbor Michael; Obieshi, Eregbuonye; Ogbemudia, Isaac Ottah; Aidonojie, Paul Atagamen (NIU Journal of Humanities; Vol 8 No 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023DO - 10.58709/niujhu.v8i4.1729, 2023)
The EndSARS protests that swept across Nigeria in [insert year] marked a pivotal moment in the nation's history, representing a collective outcry against systemic police brutality and an impassioned demand for justice and accountability. Rooted in the discontent with the Special Anti-Robbery Squad (SARS), the movement garnered unprecedented momentum, drawing diverse groups into a unified call for societal change. However, given the current Nigeria situation after the EndSARS protest, does it p and social media activisming impact on the socio-political landscape of Nigeria? It is in this regard, that this study adopts a comprehensive approach, combining qualitative and quantitative analyses to provide a nuanced understanding of the motivations behind the protests, the profile of the protesters, and the strategies employed to amplify their voices. Concerning this, ……. questionnaires were distributed among the respondents and the result obtained was analyzed using a descriptive and analytical method. The findings of the study unravel the intricacies of the EndSARS protests, shedding light on the diverse backgrounds of the participants and their shared grievances which is necessitated by bad governance. Furthermore, it assesses the immediate and long-term impacts of the protests on policy reforms, public perception, and the overall discourse surrounding governance and accountability in Nigeria. The study further conclude and recommend the need for a transformative potential of grassroots movements in challenging systemic issues. It emphasizes the need for sustained efforts to address the root causes of social discontent and advocates for continued civic engagement to ensure lasting change. It was further recommended that there is a need to include policy reforms, institutional changes, and ongoing dialogue between the government and civil society to build a more just and accountable society. Keywords: EndSARS, Protests, Governance, Nigeria